Constructing trustworthy historical narratives: criteria, principles, and techniques - Gill, Michael J.; Gill, David James; Roulet, Thomas J. (Wiley, 2018)
Organizational scholars increasingly recognize the value of employing historical research. Yet the fields of history and organization studies struggle to reconcile. In this article, we contend that a closer connection between these two fields is possible if organizational historians bring their role in the construction of historical narratives to the fore and open their research decisions up for discussion. We provide guidelines to support this endeavor, drawing on four criteria that are prevalent within interpretive organization studies for developing the trustworthiness of research: credibility, confirmability, dependability and transferability. In contrast to the traditional use of trustworthiness criteria to evaluate the quality of research, we advance the criteria to encourage historians to generate more transparent narratives. Such transparency allows others to comprehend and comment on the construction of narratives thereby building trust and understanding. We convert each criterion into a set of guiding principles to enhance the trustworthiness of historical research, pairing each principle with a practical technique gleaned from a range of disciplines within the social sciences to provide practical guidance.